Chapter La Resistenza raccontata a scuola dai partigiani: esperienze del passato e prospettive per il futuro - Oliviero, Stefano (Public History of Education. Teorie, esperienze, strumenti, 2022)
The paper attempts to give some useful coordinates to start reconstructing the history of Resistance experiences (meetings, educational and teaching activities) as told at school by its protagonists. The paper also puts forward some educational and didactic proposals for the future. The privileged point of observation is the activity of the National Association of Italian Partisans (ANPI), the main Italian resistance association founded in 1944 to bring together the protagonists of the armed struggle against Nazi-fascism.